What the wife knew : a novel - Kane, Darby (William Morrow, an imprint of HarperCollinsPublishers, 2024)
"Dr. Richmond Dougherty is a renowned pediatric surgeon, an infamous tragedy survivor, and a national hero. He's also very dead - thanks to a fall down the stairs. His neighbors angrily point a finger at the newest Ms. Dougherty, Addison. The sudden marriage to the mysterious young woman only lasted ninety-seven days, and he'd had two suspicious "accidents" during that time. Now Addison is a very rich widow. As law enforcement starts to circle in on Addison and people in town become increasingly hostile, sides are chosen with Kathryn, Richmond's high school sweetheart, wife number one, and the mother of his children, leading the fray. Despite rising tensions, Addison is even more driven to forge ahead on the path she charted years ago ... Determined at all costs to unravel Richmond's legacy, she soon becomes a target-with a shocking note left on her bedroom wall: You will pay. But it will take a lot more than faceless threats to stop Addison. Her plan to marry Richmond then ruin him may have been derailed by his unexpected death, but she's not done with him yet"--